FEMINITAS DAN MAKEUP PADA ANIMASI NUSSA RARRA EPISODE: GIRLS TALK - Yosieana Duli Deslima (Fakultas Dakwah dan Komunikasi, 2020)
This study aims to describe the form of the meaning of femininity contained in the animation